The Unveiling of Secrets (Kashf al-Asrār) : The Visionary Autobiography of Rūzbihān al-Baqlī (1128-1209 A.D.) - Papan-Matin, Firoozeh (Islamic History and Civilization, 2006)
The Unveiling of Secrets ( Kashf al-Asrār ) is the visionary autobiography of one of the most significant mystics of twelfth-century Iran, Rūzbihān al-Baqlī (522/1128-606/1209). Written in Arabic, it describes the life of the author primarily as comprised of his mystical visions. Rūzbihān depicts himself in the unseen world ( ʿālam al-ghayb ) in the company of God, saints, prophets, and angels. His self-portrait in this manner communicates his special status with God. The sublime quality of these visions is well captured in the style of Kashf al-Asrār : the writing is simultaneously simple and clear, but eloquent and rich with extraordinary images. This is the first critical edition of the manuscipt of Kashf al-Asrār which provides an intriguing case in the genre of Islamic autobiographies.